Protective Effects of Lanosterol Synthase Up-Regulation in UV-B-Induced Oxidative Stress - Hua, Hui; Yang, Tianyao; Huang, Liting; Chen, Rentong; Li, Menglin; Zou, Zhenzhen; Wang, Nan; Yang, Dan; Liu, Yang (Frontiers in Pharmacology, 2019)
UV-B radiation may be an important risk factor in cataracts aetiology. After exposure to UV-B radiation, cells show imbalances in the repair of DNA damage, which induce changes in the levels of certain proteins, including alpha-crystallin, which is the most abundant protein in the lens and crucial for the maintenance of lens transparency. Lanosterol synthase (LSS), an essential rate-limiting enzyme in cholesterol biosynthesis, might play significant roles in oxidative stress and in the maintenance of lens transparency. However, the roles of LSS in UV-B-induced apoptosis are not well understood. Therefore, we irradiated female Sprague-Dawley rats with ultraviolet radiation to establish an animal model for exploring the variations in LSS expression during the early stages of UV-B exposure. In addition, we cultured human lens epithelial (HLE) cells that overexpress LSS and exposed them to UV-B radiation to explore the function of increased LSS expression in UV-B-induced apoptosis. The data demonstrated that UV-B exposure induced oxidative stress and apoptosis in rat lens epithelial cells and that irradiance exposure increased the level of lenticular damage. Additionally, UV-B exposure decreased the alpha-crystallin content and increased the expression of Bax and cleaved Caspase-3 compared with the control levels. After exposure to UV-B, the apoptosis-related index of HLE cells overexpressing LSS was lower than that of the control cells. Furthermore, ROS overproduction might activate the Sirtuin 1 (Sirt1) pathway, which induced protein expressions of sterol regulatory element binding transcription factor 2 (SREBF2), 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGCR) and LSS. However, the specific mechanism of the Sirt1 pathway needed to be further studied. In summary, UV-B exposure induced oxidative injury and resulted in crystallin denaturation and apoptosis in lens epithelial cells, and LSS might play a protective role during the early stages of this process and could be an important target in the cataracts prevention.